Relationship between body composition and 100-m-running time in elite female sprinter: A 7-year retrospective study - Abe, T.; Harada, Y.; Kawamoto, K.; Fukashiro, S. (Medicina Sportiva, 2011)
Aim of the study: To report on the relationship between body composition and 100-m running time in an elite female sprinter using 7 years of data. Methods: The subject was a 3-time participant in the Track and Field World Championship and a 2-time participant in the Asian Games. Since track and field in Japan is a spring (May-June) and autumn (September-October) sport, we recorded her best 100-m time in both seasons. During the study, her personal best and mean season best times were 11.39 sec and 11.59 sec, respectively. Subcutaneous fat and muscle tissue thicknesses were measured by ultrasound in each season. Body density was estimated from FTH using an ultrasound-derived prediction equation, and the body fat percentage (BF%) and fat-free mass (FFM) were calculated. Total and segmental (arm, trunk, thigh, and lower leg) skeletal muscle mass (SMM) was estimated from MTH using prediction equations. Results: There was a positive correlation between 100-m sprint time and fat mass and BF% (r = 0.64, P = 0.04 and r = 0.67, P = 0.02, respectively). A regression expression between BF% and 100-m time was: 100-m time [sec] = 9.92 + 0.11·BF%. Total and lower body SMM did not correlate with the 100-m time (r = 0.04, P = 0.91 and r = 0.05, P = 0.87, respectively). Conclusion: Thus, BF% was a strong predictor of 100-m sprint performance in an accomplished elite female runner. Using a regression formula, we determined that 1% excess body fat is nearly equivalent to a 0.11-sec reduction in 100-m sprint time.